Recreational Reward-Based Motivation: a Strategy for Strengthening Motivation among High-Achieving Students at Child Pesantren - Taufikin Taufikin (Educazione: Journal of Education and Learning, 2023)
The practice of rewarding students in Islamic boarding schools often remains merely symbolic and has yet to foster meaningful experiences. This gap opens up opportunities to explore how recreational activities can serve as a more dynamic and sustainable motivator for students. This study aims to analyze the role of recreational rewards in shaping the motivation of high-achieving students at PPATQ Raudlatul Falah Pati. The approach used is a qualitative case study involving observations of more than 500 students, interviews with one kiai, four ustaz, five students, and five parents, and an analysis of academic documents and tahfidz achievements. The results indicate that recreation-based rewards function as multidimensional motivators. Academically, students ranked 1–5 demonstrated improved learning strategies and consistent achievement. Regarding Quran memorization, twice-yearly exams fostered a more structured review routine. In the social sphere, participation in boarding school activities, such as haflah, expanded the meaning of achievement beyond the classroom. Meanwhile, indicators of punctuality through early arrival formed a new habitus supported by families. Recreation became an anticipated emotional experience and a symbol of collective recognition of students’ efforts. Its implications point toward a transformation of the reward approach in Islamic boarding schools from mere incentives into a pedagogical strategy that shapes character and sustains achievement.